2013
DOI: 10.1095/biolreprod.113.108696
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiles of the Embryonic Chorioamnion and Uterine Caruncles in Buffaloes (Bubalus bubalis) with Normal and Retarded Embryonic Development1

Abstract: The aim of this study was to compare the proteome profiles of the chorioamnion and corresponding caruncle for buffalo embryos that had either normal or retarded development on Day 25 after artificial insemination (AI). In experiment 1, embryos that were to subsequently undergo late embryonic mortality had a smaller width on Day 25 after AI than embryos associated with pregnancy on Day 45 after AI. In experiment 2, 25 Italian Mediterranean buffaloes underwent transrectal ultrasonography on Day 25 after AI, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 87 publications
5
38
1
4
Order By: Relevance
“…The results obtained in this study demonstrated that reproductive status (pregnant, not pregnant and LEM) and progesterone blood levels were not affected by the different space allowance conditions. On the contrary, P4 blood levels were significantly higher in pregnant buffaloes, compared to not pregnant and buffaloes underwent LEM, in agreement with other studies (Vecchio et al, 2012;Balestrieri et al, 2013). These findings support the hypothesis that LEM in buffalo is primarily due to a reduced P4 secretion by the ] LDG HDG corpus luteum.…”
Section: P Valuesupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained in this study demonstrated that reproductive status (pregnant, not pregnant and LEM) and progesterone blood levels were not affected by the different space allowance conditions. On the contrary, P4 blood levels were significantly higher in pregnant buffaloes, compared to not pregnant and buffaloes underwent LEM, in agreement with other studies (Vecchio et al, 2012;Balestrieri et al, 2013). These findings support the hypothesis that LEM in buffalo is primarily due to a reduced P4 secretion by the ] LDG HDG corpus luteum.…”
Section: P Valuesupporting
confidence: 91%
“…These findings support the hypothesis that LEM in buffalo is primarily due to a reduced P4 secretion by the ] LDG HDG corpus luteum. Adequate luteal function and threshold circulating concentrations of P4 in circulation are required to guarantee an uterine environment that promotes ongoing elongation of the embryo during the critical peri-implantation period of pregnancy (Balestrieri et al, 2013). In our study no differences were found on blood metabolities and redox status between buffaloes maintained in high and low density.…”
Section: P Valuecontrasting
confidence: 59%
“…Differences in proteome profiles were also reported for the caruncles adjacent to the chorioamnions of embryos with retarded and normal growth. Differentially expressed proteins were related to antioxidant protection, protease inhibition and protein folding [13]. These findings supported other evidence that a disruption of conceptus-uterus interaction, as a result of reduced progesterone, is the major cause of late embryonic mortality in buffaloes [1], [2].…”
Section: Introductionsupporting
confidence: 85%
“…The latter covers the period during which there is maternal recognition of pregnancy. It was proposed that late embryonic mortality in buffaloes results from the failure of embryonic attachment [2], [13] which is a consequence, at least in part, of reduced concentrations of P4 in circulation from around Day 10 after mating [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation